Ciências naturais na região das ilhas de Abaetetuba-PA: uma abordagem do ensino modular - SENA, Ana Maria Lobo (2024)
The objective of the present work was to address the teaching of natural sciences in the islands of Abaetetuba-PA, in the context of modular teaching and to verify this educational reality experienced day by day by students and teachers. The methodology adopted was elaborated a substructured questionnaire and made the interview with the teachers and students. The choice of this work proposal took into account the lack of information about the teaching of science in the islands and how the modular teaching contributes in the riverside environment, since there is no diagnosis of the teaching of science which makes it difficult to analyze more Coherent and needs this reality. In this way, a contextualized view of the teaching of science in the islands of Abaetetuba-PA is offered in the context of modular teaching, which will serve as a reference for future interventions in this field of research that will improve the education system experienced by Inhabitants of the islands.